1987
DOI: 10.1111/j.1748-1716.1987.tb08208.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow changes in the dental pulp of the cat and rat measured simultaneously by laser Doppler flowmetry and local 125I clearance

Abstract: Blood flow changes in the dental pulp of lower canine teeth of mature cats and incisors of mature rats were investigated with simultaneous laser Doppler flowmetry and local 125I-clearance (wash-out) during electrical sympathetic stimulation, efferent stimulation of n. alveolaris inferior (IAN) (cats) and i.a. infusions of substance P (SP) (cats). Stimulation (1-4 Hz, 4 V., 1.5 ms) of the cervical sympathetic trunk produced frequency-dependent decreases in both laser Doppler output and disappearance rate of iod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…A vasoconstrictor response in the dental pulp and oral mucosa was provoked by activation of the sympathetic nerves in experimental animals. Here, in addition to noradrenalin, neuropeptide Y probably is involved in sympathetic vascular control in oral tissues [29].…”
Section: Discussionmentioning
confidence: 99%
“…A vasoconstrictor response in the dental pulp and oral mucosa was provoked by activation of the sympathetic nerves in experimental animals. Here, in addition to noradrenalin, neuropeptide Y probably is involved in sympathetic vascular control in oral tissues [29].…”
Section: Discussionmentioning
confidence: 99%
“…The masseter muscle was ascertained by the naked eye. The LDF values obtained in this way represent the blood flow in the superficial vessels of the masseter muscle (8,22). Electrical calibration for zero blood flow was performed for all recordings.…”
Section: Methodsmentioning
confidence: 99%
“…One of the major draw backs of this technique is that measurement results can not be expressed in absolute units but must instead be giv en in arbitrary units based on the calibration of the machine in a zero reflectance and a standard motility solution. Nonetheless, the accuracy and reliability of LDF in measuring blood flow in teeth has been confirmed in animal models by comparing the technique with other methods used to measure the perfusion of the dental pulp [2,3]. Clinical applications of LDF in dentistry have been primarily in the area of traumatology, where it has been used to monitor pulp vitality in luxated teeth over time [4,5], A recent study has reported the accuracy of LDF in distinguishing between vital and nonvital teeth [6].…”
Section: Introductionmentioning
confidence: 97%